Sustainable Technologies for the Management of Agricultural Wastes (Applied Environmental Science and Engineering for a Sustainable Future,, 2018)
This book discusses modern technologies for utilizing various types of agricultural waste as a direct means of properly managing its abundance. It explores the potential of using waste materials obtained from the palm oil industry, used cooking oil, maize and tea plantations, as well as citrus-based plants for the production of useful, high-value materials such as pyroligenous acid and bio-oil (Chapter 1), ferulic acid (Chapter 4) and bio-control agents (Chapter 5-7, 9). It also includes case studies to further enhance readers' understanding. This comprehensive volume is useful to anyone involved in agricultural waste management, green chemistry and agricultural biotechnology. It is also recommended as a reference work for all agriculture and biotechnology libraries.